(untitled) (Acta Entomologica Serbica, 2023)
This study offers a comprehensive guide to the identification of 34 Aphidius species that were found in the territory of Serbia. Also, for all Aphidius species, a total of 97 aphid hosts were represented. Aphidius linosiphonis Tomanović & Starý and Aphidius balcanicus Tomanović & Petrović were described from Serbia. Aphidius ericaphidis Pike & Starý and A. banksae Kittel are allochthonous species in Serbia of North American and Asian origin, respectively. For both allochthonous species, the first records for the fauna of Europe were from Serbia.